Wage Award Polices Of 5-Star Hotel Enterprises Operating in The Accomodation Sector In Istanbul And Their Effect On Worker Satisfaction (Sample Study: Comparison Between Chosen Pilot Hotels) - Yazıcı, Hacer Neyir; Çedikçi Fener, Tuğba; Özgan, Burcu Beste (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2011)
Wages and rewarding in the labour-intensive tourism sector are not only motivating for workers but also influential in helping them to cling to life and their work. In tourism sector, like in all sectors, worker satisfaction is reflected on the enterprise. Wage awards lead to the satisfaction of workers in the tourism sector and especially in large accommodation enterprises. When we look at the same wage awards from the point of view of employers, we see that they are regarded as expense item. Wage awards, which are important for both workers and employers, are provided to workers in large hotel enterprises according to various policies. In the study which will be carried out by choosing 5-star pilot hotels already serving the sector in Istanbul, the centre of Turkish tourism; issues such as wage policies of hotel's, wage award policies and worker satisfaction will be discussed by comparison. In addition to extensive literature analysis, interviews with the chosen pilot hotels and the data obtained as a result of research will be expressed.
Keywords: human resources in tourism; employee satisfaction; wage policie; turizmde insan kaynakları; çalışan memnuniyeti; ücret politikası